BUSINESS PLAN DEVELOPMENT FOR E-COMMERCE PLATFORMS WWW.ADVENTURESTOCK.COM - Sembiring, Raja Agus Lukasta; Pefriyadi, Pefriyadi; Sembiring, Yasinta Aprilia (PT. Altin Riset Publishing, 2024)
The e-commerce platform business is experiencing rapid growth along with the development of the information technology era. With the increase in the number of middle-class people in Indonesia who use smartphones and access the internet for online shopping purposes. Data from the Ministry of Tourism of the Republic of Indonesia states that there is an increase in the number of domestic tourists. The trend of the younger generation who like outdoor activities such as traveling and adventuring. All of these opportunities were realized by the author into a business plan for the e-commerce platform www.Adventure-Stock.com. The business plan aims to produce an e-commerce platform www.Adventure-Stock.com. The method used in the formulation of this business plan is to use the e-commerce platform business observation method and outdoor activity equipment product stores. The focus group method aims to understand the needs, and desires, and obtain suggestions about the e-commerce platform. Suggestions from FGD participants are used to improve the e-commerce platform www.Adventure-Stock.com. The result of the business plan is an e-commerce platform www.Adventure-Stock.com that sells traveling and adventuring equipment products.